2013
DOI: 10.1016/j.biomaterials.2012.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Cell specific cytotoxicity and uptake of graphene nanoribbons

Abstract: The synthesis of oxidized graphene nanoribbons (O-GNR) via longitudinal unzipping of carbon nanotubes opens avenues for their further development for a variety of biomedical applications. Evaluation of the cyto- and bio-compatibility is necessary to develop any new material for in vivo biomedical applications. In this study, we report the cytotoxicity screening of O-GNRs water-solubilized with PEG-DSPE (1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)]), using six different assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
116
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(129 citation statements)
references
References 29 publications
7
116
0
1
Order By: Relevance
“…Alamar Blue assay is an ideal approach to quantitatively measure proliferation and metabolic status of cells, especially for cells cultured in suspension (such as MEL cells used in the current study). 27,28 Similar to the results of cell number counting, the Alamar Blue assay suggested that the concentration of half maximal inhibition on cell viability was greater than 10 μg/mL ( Figure 5B, P < 0.01). In contrast to nAg, MEL cells are fairly vulnerable to Ag ions (in AgNO 3 ) at even very low concentrations (0.08 μg/mL), with significant reduction in cell viability in comparison to the control ( Figure 5C, P < 0.05), and cell viability was dramatically impaired by Ag ions at 1.2 μg/mL ( Figure 5C, P < 0.001).…”
Section: Resultssupporting
confidence: 71%
“…Alamar Blue assay is an ideal approach to quantitatively measure proliferation and metabolic status of cells, especially for cells cultured in suspension (such as MEL cells used in the current study). 27,28 Similar to the results of cell number counting, the Alamar Blue assay suggested that the concentration of half maximal inhibition on cell viability was greater than 10 μg/mL ( Figure 5B, P < 0.01). In contrast to nAg, MEL cells are fairly vulnerable to Ag ions (in AgNO 3 ) at even very low concentrations (0.08 μg/mL), with significant reduction in cell viability in comparison to the control ( Figure 5C, P < 0.05), and cell viability was dramatically impaired by Ag ions at 1.2 μg/mL ( Figure 5C, P < 0.001).…”
Section: Resultssupporting
confidence: 71%
“…In vitro drug delivery studies were conducted using 50 µl of O-GNR-PEG-DSPE solution at a potential therapeutic dosage of 50 µg/ml (determined from previous cytotoxicity studies for O-GNR-PEG-DSPE[10]) loaded with 40% Dox by weight (20 µg/ml); treatment duration was 24 hours and the solution was studied in 11 cell lines (Table 1, cell line selection criteria for these studies were based on previous results). Since HeLa is a cervical cancer cell line with an integrated HPV genome, we chose cell lines comprised of cervical cancers cells with or without an HPV genome, and non-cervical cancer cells with low, normal or high EGFR expression[1828].…”
Section: Resultsmentioning
confidence: 99%
“…We used a lactate dehydrogenase (LDH) assay to assess cytotoxicity due to cellular delivery of Dox. LDH, a cytoplasmic marker for membrane integrity, provides an indirect means of assessing cytotoxicity[10]. Leaky membranes of damaged or dead cells show increased LDH release into surrounding media compared to normal intact cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations